1990
DOI: 10.1002/hep.1840110506
|View full text |Cite
|
Sign up to set email alerts
|

The Ursodeoxycholate Dose–Dependent Formation of Ursodeoxycholate–Glucuronide in the Rat and the Choleretic Potencies

Abstract: The reason for the discrepancy between bile flow and biliary bile acid excretion during ursodeoxycholate infusion in rats is unknown. We found that ursodeoxycholate-glucuronide is formed during ursodeoxycholate infusion at higher doses. Ursodeoxycholate infusion (1 to 3 mumol/min/100 gm body weight) for 90 min caused marked hypercholeresis, and the previously reported discrepancy between bile flow and biliary bile acid excretion was observed when bile acid concentrations were measured by regular enzymatic meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1990
1990
1995
1995

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…By contrast, Hayakawa [28] reported that UDC markedly inhibited biliary cefotiam excretion in rats. The reason for this discrepancy may be due to his usage of a high dose of UDC, which we previously reported to cause exten sive glucuronidation of this bile acid [29,30]. Since 3-glyA-LC inhibited biliary CPM excre tion in the present study, UDC glucuronide may have inhibited biliary CPM excretion in his study [28].…”
Section: Discussionmentioning
confidence: 70%
“…By contrast, Hayakawa [28] reported that UDC markedly inhibited biliary cefotiam excretion in rats. The reason for this discrepancy may be due to his usage of a high dose of UDC, which we previously reported to cause exten sive glucuronidation of this bile acid [29,30]. Since 3-glyA-LC inhibited biliary CPM excre tion in the present study, UDC glucuronide may have inhibited biliary CPM excretion in his study [28].…”
Section: Discussionmentioning
confidence: 70%
“…Any choleretic agent should increase bicarbonate output in bile by this mechanism. In our opinion, the experiments of Takikawa, Sano and Yamanaka (32) indicate that formation of the 3-glucuronide may occur during UDCAinduced hypercholeresis, but that the 3-glucuronide has exactly the expected choleretic activity of a bile acid 3-glucuronide and its formation is unlikely to play any causal role in the observed hypercholeresis. Thus, the experimental data of Takikawa, Sano and Yamanaka are completely in agreement with the views presented in this paper and with our previous papers dealing with hypercholeresis (2, 3, 5, 7 , 8 ) .…”
Section: Discussionmentioning
confidence: 70%
“…The choleretic activity of the taurine conjugate of nor-UDCA (5) and of UDCA (12) is similar to that of other taurine conjugates of the common natural bile acids. As noted above, Takikawa, Sano and Yamanaka have also reported that the 3-glucuronide of UDCA has choleretic properties similar to those of other bile acid amidates when allowance is made for the two negative charges of the 3-glucuronide (32). Hypercholeresis has also been attributed to stimulation of canalicular bicarbonate secretion by the accumulation of unconjugated UDCA in the hepatocyte (4, 10,11).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…6B). Formation of CDC-gl was also confirmed by negative-ion fast-atom bombardment-mass spectrometry analysis of the bile according to the presence of m/z 567 and m/z 589, [M-HI-of dihydroxy bile acid glucuronide and its sodium salt, respectively, as previously reported (26,27). Table 2 summarizes the conjugation of [ 14C]CDC in the bile.…”
Section: Resultsmentioning
confidence: 91%